Identification and Optimization Control of a 12-Volt DC Motor System Using Linear Quadratic Regulator for Community Empowerment - Muhammad Bilhaq Ashlah; Rama Arya Sobhita; Anggara Trisna Nugraha (Maritime in Community Service and Empowerment, 2025)
Direct current (DC) motors are among the most commonly utilized electric motors in various industries due to their robust and reliable regulatory characteristics. These motors also hold significant potential for application in community-based programs, particularly in renewable energy and small-scale mechanization projects that aim to empower underprivileged communities. To effectively analyze a DC motor system, it is essential to mathematically model its operational variables. This mathematical model is expressed as a transfer function, which is integrated into the simulation process using the Matlab Simulink platform. Typically, first- and second-order equations are used to represent these transfer functions. The optimization process involves the state-space representation to determine the K gain value, which is critical for achieving precise control. The Q value, derived from the multiplication of the C transpose and C matrix, directly influences the system's step response speed, while the R value is predetermined at 0.000001. Adjusting these parameters enables an optimized balance between response speed and system stability. This research provides a foundational framework for leveraging DC motor optimization in real-world applications, particularly in community empowerment programs. By enabling more efficient control mechanisms, this study contributes to the development of affordable and sustainable energy solutions, such as small-scale irrigation systems, local production facilities, or microgrid systems in remote areas.